Storytelling or the diverted narrative - Tebbani, Ali (Journal of Human Sciences, 2021)
Storytelling in narrative communication is not the art of storytelling. It is a technique based on an instrumentalized strategic use of the story. A technique that developed in the business world across the Atlantic 25 years ago, before spreading to politics and media discourse in general. The principle of storytelling anglicism is the diversion of narration and in fact, it clearly marks the difference with the art of storytelling, by producing neither more nor less of the counter-narrative. In the political and media fields, the art of storytelling has become the mode of manipulation par excellence for crowds, orchestrated by the “spin doctors” who control information within the media by addressing voters directly and by fabricating opinion. Storytelling is also intended for consumers lacking benchmarks. Management circles have seized on this discipline to impose the art of storytelling as a mode of communication in the market economy and the world of work.